Thomas North’s travel to Rome (1555): From itinerary to traveler’s memoir - A. Yu. Seregina (Шаги, 2023)
The article analyses the text of the «Journey of the English Ambassadors to Rome in 1555» – a travel memoir compiled in the 1560s on the basis of a diary kept by Thomas North (1535 – c.1601), then a page in the household of ambassador Thomas Thirlby, Bishop of Ely. Later in life, Thomas North became famous as the author of the first, often reprinted English translation of Plutarch’s «Parallel Lives» (1579), and his travelogue remains the most important of the extant documents related to the last English embassy to Rome (1555), which temporarily restored the country’s relationship with the Holy See. However, the «Journey» has been poorly studied and has never been looked at in the context of travel literature. Detailed analysis of North’s text shows that although the author followed the genre of medieval itineraries his work differs in focus and intent from other travel diaries and memoirs produced by English travelers and diplomats of the mid-16th century. North was not much interested in the political side of his journey, or even in the Roman antiquities. His text presents a series of the author’s impressions of what he saw in France, Italy, Germany and the Netherlands, of new palaces, fortresses, instruments, mechanisms and «wonders»: objects, animals and birds, and social practices. The unique combination of itinerary, diary and memoir in North’s «Journey» demonstrates how 16th century Europeans manipulated literary genres in search of a form suitable for describing their travel experiences and tastes.